Diagnostic dilemmas in cardiology. (9th August 2012) - Costopoulos, Charis; Benson, Adam; Prasad, Sanjay; Ghuran, Azad
Abstract : A 29-year-old pregnant woman presented in accident and emergency with severe acute left ventricular failure requiring admission to the intensive care unit. A nasal swab was found to be positive for H1N1 making peripartum and viral cardiomyopathies, the most likely differential diagnoses. CT coronary angiography and subsequent invasive angiography revealed an anomalous coronary system thus making ischaemic cardiomyopathy also a possibility. Cardiac MRI played a vital role in identifying the underlying cause, which in this case was that of H1N1 influenza cardiomyopathy. Correct diagnosis in such patients is paramount as this impinges on patients' overall prognosis. In this case aggressive initial therapy including inotropic support and invasive ventilation followed by standard antifailure treatment with β-blockers and angiotensin-converting enzyme inhibitors led to restoration of the patient's left ventricular function and an associated marked improvement in symptoms.